Efficacy of pulmonary rehabilitation in improving the quality of life for patients with chronic obstructive pulmonary disease: Evidence based on nineteen randomized controlled trials. (January 2020) - Dong, Jige; Li, Zhanjun; Luo, Lihua; Xie, Hongzhi
Abstract: Background: Increasing studies have shown that application of pulmonary rehabilitation may improve the quality of life of chronic obstructive pulmonary disease (COPD) patients. However, the results of some studies still remained controversial and sample size of them limited to small number of participants. A systematic review and meta-analysis was designed to evaluate the efficacy of pulmonary rehabilitation for improving the quality of life in patients with COPD. Methods: We searched the Cochrane Library, PubMed, EMBASE and Web of Science up to March 29, 2019 to identify relevant randomized controlled trials (RCTs) analyzing and evaluating the efficacy of pulmonary rehabilitation (PR) in patients with COPD. Participants were randomly assigned to receive PR (intervention group) or usual care (controller group). We used St. George's Respiratory Questionnaire (SGRQ) scores as evaluating indicators of quality of life. Mean differences (MDs) with 95% confidence intervals (CIs) were estimated to compare the outcomes of the groups. We also performed subgroup analysis for the pooled results of pulmonary rehabilitation effects in COPD patients. Besides, sensitivity analysis was performed to examine the stability of the combined results. Two reviewers assessed trial quality and extracted data independently. All statistical analyses were performed using standard statistical procedures provided in Review Manager 5.2 and Stata 12.0. Results: Nineteen randomized controlled trials (N = 1146 participants) were identified for the present analysis. Comparing pulmonary rehabilitation groups with usual care groups (control groups), statistically significant improvements were noted in total score of SGRQ, with MD of −6.53. In addition, life quality improvement of SGRQ scores was better than 5 units in symptoms score, impacts score and activity score, with MDs of −5.01, −7.23 and −6.08, respectively. Conclusions: Rehabilitation may constitute one of important components of the management of COPD and may be beneficial in improving the quality of life. Future research should focus on identifying which components of pulmonary rehabilitation are essential, its ideal length and location, the degree of supervision and intensity of training required and how long treatment effects persist. Highlights: Rehabilitation may constitute one of important components of the management of COPD. Rehabilitation may be beneficial in improving the quality of life. Both hospital and community exercise are effect in improving the quality of life for COPD patients. Patients receiving exercise combined with other activity may experience more effectiveness than exercise only.